1983
DOI: 10.1007/bf00975661
|View full text |Cite
|
Sign up to set email alerts
|

Radiological findings in the hand in seckel syndrome (bird-headed dwarfism)

Abstract: Two patients with severe intrauterine growth retardation and bird-headed appearance are described. These two children had most of the clinical features of the so-called Seckel dwarfism. The radiological findings included: (1) ivory epiphyses affecting all phalanges in one patient and many phalanges in another; (2) cone-shaped epiphyses in the proximal phalanges; (3) marked disharmonic bone maturation between carpals and phalanges, between individual carpals, and from side to side; (4) alteration in the length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…Recently, D'Angelo and Di Bartolomeo reported two cases of SCKL with intracranial anomalies, suggestive of MOPDII diagnosis 14 15. Similarly, SCKL patients with bone dysplasia suggestive of MOPDII have been reported 16 17. From our study, we suggest that the MOPDII spectrum is wider than previously defined.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, D'Angelo and Di Bartolomeo reported two cases of SCKL with intracranial anomalies, suggestive of MOPDII diagnosis 14 15. Similarly, SCKL patients with bone dysplasia suggestive of MOPDII have been reported 16 17. From our study, we suggest that the MOPDII spectrum is wider than previously defined.…”
Section: Discussionsupporting
confidence: 56%
“…Majewski et al [1982b] also described the characteristic facial features and the progressive bony dysplasia. Poznanski et al [1983] clarified the radiological changes of two affected individuals who had been reported previously by Pasquino and Iannaccone [1978] and again by Boscherini et al [1981]. Willems et al [1987] reported a family with consanguinity and suggested that there might be an autosomal recessive basis for the disorder and Verloes et al [1987] reported another consanguineous family with two affected siblings.…”
Section: Historical Perspectivementioning
confidence: 49%
“…Review of the literature produced 27 cases [Brizard et al, 1973;Anoussakis et al, 1974;Pasquino and Iannaccone, 1978; reported again by Boscherini et al, 1981;Majewski et al, 1982a;Toudic et al, 1983;and by Poznanski et al, 1983;Verloes et al, 1987;Willems et al, 1987;Herman et al, 1991;Shebib et al, 1991; reported again by Théau and Maroteaux, 1993;Al Gazali et al, 1995, Masuno et al, 1995Spranger et al, 1996;D'Angelo et al, 1998;Halder et al, 1998;Majewski and Goecke, 1998;Tekin et al, 2000;Fukuzawa et al, 2002;Kantaputra, 2002;Nishimura et al, 2003] with sufficient clinical and natural history information to be sure of the diagnosis and to contribute to defining the frequency of various features. The authors of the articles were recontacted to update clinical information and to provide additional comments on features not mentioned in the original reports.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Hand radiographs taken 4 years apart demonstrated that most of ivory epiphyses disappear as the patients aged. These age-related phenomena are similar to those of Seckel syndrome [Poznanski et al, 1983]. The reported patients share many features with an MOPD patient who was reported to have long and slender clavicles, ivory epiphyses, cone-shaped epiphyses, dislocated hip, with abnormal dental development [Shebib et al, 1991].…”
Section: Discussionmentioning
confidence: 73%